Pore‐Structure Control in Metal–Organic Frameworks (MOFs) for Capture of the Greenhouse Gas SF6 with Record Separation. Issue 33 (4th July 2022) - Wang, Shao‐Min; Mu, Xuan‐Tong; Liu, Hao‐Ran; Zheng, Su‐Tao; Yang, Qing‐Yuan
Abstract: In the electronics industry, the efficient recovery and capture of sulfur hexafluoride (SF6 ) from SF6 /N2 mixtures is of great importance. Herein, three metal–organic frameworks with fine‐tuning pore structures, Cu(peba)2, Ni(pba)2, and Ni(ina)2, were designed for SF6 capture. Among them, Ni(ina)2 has perfect pore sizes (6 Å) that are comparable to the kinetic diameter of sulfur hexafluoride (5.2 Å), affording the benchmark binding affinity for SF6 gas. Ni(ina)2 exhibits the highest SF6 /N2 selectivity (375.1 at 298 K and 1 bar) and ultra‐high SF6 uptake capacity (53.5 cm 3 g −1 at 298 K and 0.1 bar) at ambient conditions. The remarkable separation performance of Ni(ina)2 was verified by dynamic breakthrough experiments. Theoretical calculations and the SF6 ‐loaded single‐crystal structure provided critical insight into the adsorption/separation mechanism. This porous coordination network has the potential to be used in industrial applications. Abstract : The metal–organic framework (MOF) Ni(ina)2 has pore sizes (6 Å) that are perfectly compatible with the kinetic diameter of sulfur hexafluoride (5.2 Å), affording the benchmark binding affinity for this potent greenhouse gas that is used in the electronics industry.